Komitmen Beragama Tokoh Dalam Novel Atheis Karya Achdiat K. Mihardja - Fisnia Pratami; atma titisan (Universitas Lampung, 2020)
Religius comitmen is a problem in this study. the purpose of this study is to describe religious commitmen that includes the dimension of belief, practice dimension, experiece dimension, knowledge dimension, and concequence dimension. The data source of this research is Achdiat K. Mihardja. the author of Novel entitled